Air Quality and the Senses in Early Modern Italy - Rombough, Julia (Renaissance and Reformation / Renaissance et Réforme)

(untitled) (Iter Press, 2021)
Using printed and archival records, this article analyzes the sensory practices associated with air quality in sixteenth- and seventeenth-century Italy. Air pollution was a prime concern for early modern Italians, particularly in urban centres where industry, density, and frenetic sensescapes were thought to prompt chronically unhealthy airs. According to early modern experts, air quality was at the root of individual and public health. My analysis shows how Italians relied on a robust set of sonic and olfactory tools to cleanse the air and craft healthy environments. Simultaneously, a contrasting set of sounds and smells were thought to pollute the air. The sensory practices surrounding air quality reveal the highly localized and personalized nature of early modern environmental practice. This article argues that entwined social and environmental conceptions of purity and pollution shaped sensory, social, and environmental experience in the premodern city.